Navigating Emergency Management of Cancer Patients: A Retrospective Study on First-Time, End-Stage, and Other Established Diagnoses in a High Turnover Emergency County Hospital - Mihaela Corlade-Andrei; Radu-Alexandru Iacobescu; Viorica Popa; Alexandra Hauta; Paul Nedelea; Gabriela Grigorasi; Monica Puticiu; Roxana Elena Ciuntu; Andreea Ivona Sova; Diana Cimpoesu (Medicina)
Background and Objectives: The incidence and prevalence of cancers are increasing worldwide, with special emphasis placed on prevention, early detection, and the development of new therapeutic strategies that strongly impact patient outcomes. Limited data are available about emergency care’s role in treating patients with cancer. This study aims to determine the burden of end-stage and first-time diagnosis of cancer on emergency care in a high-turnover emergency care center. Materials and Methods: A retrospective observational study was conducted to identify patients requesting emergent aid for cancer-related symptoms in the Emergency Department of “St. Spiridon” Hospital from Iasi (Romania) between 1 October 2022 and 30 September 2023. The proportion and demographic characteristics of end-stage patients and those who received a first-time diagnosis during the emergency visit were evaluated. Risk analysis was performed to understand these patients’ care needs (such as medical care, surgical care, specialty consults, intensive care, ward admission, and other hospital transfers) and immediate care outcomes (such as in-hospital mortality and home discharge). Results: 2318 patients with cancer requested emergent care (patient presentation rate of 3.08%), of which 444 (19.15%) were diagnosed for the first time, and 616 (26.57%) were at the end-stage. First-time diagnosed patients had a significantly different distribution of cancer types (p < 0.001), were more likely to need any form of medical care, to require a specialty consultation, or to be admitted to a ward (OR 2.65, 95% CI: 2.12–3.32; p < 0.001; OR 3.28, 95% CI: 2.48–4.35, p < 0.001; OR 2.09, 95% CI: 1.70–2.59; p < 0.001, respectively) but were less severe, while end-stage patients were more likely to address repeatedly to the emergency room (OR 1.86, 95% CI: 1.32–2.59; p = 0.001) and had higher odds of needing intensive care, assisted ventilation and death (OR-4.63, 95% CI: 1.10–19.45, p = 0.04; OR 2.59, 95% CI: 1.57–4.28; p < 0.001, and OR 4.06, 95% CI: 1.73–9.54; p = 0.001, respectively). Conclusions: The emergency department often carries the weight of diagnosing patients with cancer and treating patients with end-stage disease. These data highlight the importance of prehospital care, particularly for cancer screening and palliative care, and the importance of fostering multidisciplinary collaboration in the emergency room with oncologists, geriatricians, and palliative care specialists to improve patient outcomes.